The theory of evolution as a scientific phenomenon - Pylypchuk, O. Ya. (History of science and technology, 2013)
In the process of development of the world his laws were complicated (for example, with the advent of atoms appeared the laws of chemistry, with advent of life – of biology, with advent of farming – of economy), and that is why the process of development of nature necessarily became complicated. It seems to be an obvious, however there is a doctrine that says something completely different: as though with the advent of life there was only one law – "the selection of casual variations" - which is simpler than the previous ones, but nevertheless has established itself in the evolution of life. These variations are declared as the only provider of evolutional changes. And although neither Ch. Darwin, the founder of the doctrine of evolution of the organic world, nor his followers did not cite a single example, where evolution proceeds in exactly this way, and not otherwise, although there are examples that this is nevertheless not so, the doctrine of evolution became dominate in biology and dominates until now. Why? The answer to this question is in our article – in the view of the theory of еvolution as a scientific phenomenon.